Interaction of indoor air contaminants and respiratory health among children in the daycare centers - Mohd Najib, Siti Aiman Husna; Jalaludin, Juliana; Feisal, Nur Azalina Suzianti; Faruk, Tashnia; Khan, Md Firoz (Springer Science and Business Media, 2024)
Apart from homes, daycare centers (DCCs) serve as essential indoor environments for children. The objective of this study was to investigate the correlation between IAQ and respiratory health implications in children and to identify patterns in IAQ using chemometric analysis. A total of 100 children aged 4 to 6 from 5 urban DCCs in Petaling Jaya, Selangor, were included in the study. The selected IAQ variables comprised temperature, humidity, air velocity, particulate matter, carbon dioxide (CO2) levels, airborne bacteria, and fungi. Reported respiratory health symptoms were collected along with sociodemographic and exposure history. There was a significant difference in the median concentration of PM10, PM2.5, temperature, and relative humidity (p = 0.035; p = 0.008; p < 0.001; p < 0.001) among DCCs. DCC B recorded the highest concentration of PM10, PM2.5, airborne fungi, and temperature which exceeded the standard guidelines. The prevalence of cough (χ22 = 12.810, p = 0.012), running nose (χ22 = 11.130, p = 0.013), and blocked nose (χ22 = 11.097, p = 0.025) were significantly higher among DCCs. Statistical results showed that there was a significant association between cough and running nose with high concentrations of PM10 and PM2.5. The chemometric analysis of HCA showed that DCC C was found to have the highest dissimilarity in IAQ pollutants. PCA identified that PM2.5, PM10, airborne fungi, air velocity, and temperature have positive coefficients, accounting for 92.3% of DCCs located on the roadway and ongoing construction. The findings highlight the importance of maintaining good IAQ in DCCs to promote children's respiratory health and develop interventions and policies. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature B.V. 2024.